The adventures of Dr. sloth : Rebecca Cliffe and her quest to protect sloths - Eszterhas, Suzi (2022)
"Scientists know surprisingly little about sloths, but Becky Cliffe is working to change that. Visit the steamy jungles of Central and South America to see these adorable animals up close--and find out ways to protect them"--
Includes bibliographical references and index.
Ages 8-12
Grades 4-6
Keywords: Cliffe, Rebecca -- Juvenile literature; Sloths -- Juvenile literature; Sloths -- Research -- South America -- Juvenile literature; Sloths -- Research -- Central America -- Juvenile literature; Sloths -- Conservation -- Juvenile literature; Zoologists -- Great Britain -- Biography -- Juvenile literature